2020
DOI: 10.1186/s12936-020-03414-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reduction of malaria transmission following the introduction of indoor residual spraying in previously unsprayed districts: an observational analysis of Mopti Region, Mali, in 2017

Abstract: Background The National Malaria Control Programme (NMCP) of Mali has had recent success decreasing malaria transmission using 3rd generation indoor residual spraying (IRS) products in areas with pyrethroid resistance, primarily in Ségou and Koulikoro Regions. In 2015, national survey data showed that Mopti Region had the highest under 5-year-old (u5) malaria prevalence at 54%—nearly twice the national average—despite having high access to long-lasting insecticidal nets (LLINs) and seasonal malaria chemoprevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…More recently, a number of observational studies have reported benefits of using IRS with pirimiphos-methyl (Actellic 300CS®). In the Mopti Region of Mali, delivery of a single round of IRS with Actellic 300CS® was associated with a 42% decrease in the peak incidence of laboratory confirmed malaria cases reported at public health facilities 34 . In the Koulikoro Region of Mali, villages that received a single round of IRS with Actellic 300CS® combined with LLINs observed a greater than 50% decrease in the incidence of malaria compared to villages that only received LLINs 35 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More recently, a number of observational studies have reported benefits of using IRS with pirimiphos-methyl (Actellic 300CS®). In the Mopti Region of Mali, delivery of a single round of IRS with Actellic 300CS® was associated with a 42% decrease in the peak incidence of laboratory confirmed malaria cases reported at public health facilities 34 . In the Koulikoro Region of Mali, villages that received a single round of IRS with Actellic 300CS® combined with LLINs observed a greater than 50% decrease in the incidence of malaria compared to villages that only received LLINs 35 .…”
Section: Discussionmentioning
confidence: 97%
“…In Western Kenya, the introduction of a single round of IRS with Actellic 300CS® was associated with a 44-65% decrease in district level malaria case counts over a 10 month period compared to pre-IRS levels 38 . In addition, several recent reports have documented dramatic resurgences following the withdrawal of IRS with bendiocarb in Benin 39 , and the withdrawal of IRS with Actellic 300CS® in Mali and Ghana 34,36 .…”
Section: Discussionmentioning
confidence: 99%
“…For example in 2015, the odds for malaria infection (active and past combined) in our study were eight-fold higher (p = 0.001) than in 2018. In 2015, the Mopti Region had twice the malaria prevalence, compared to the national average, for children under ve years, prompting an indoor residual spraying program which took place in 2017 and included the Bandiagara district [24]. From 2016 to 2017, peak malaria incidence decreased by 42%, on average, in sprayed health facility catchment areas compared to non-sprayed communities in the Mopti Region [24].…”
Section: Discussionmentioning
confidence: 99%
“…A new microencapsulated formulation of pirimiphos-methyl was later developed (Actellic® 300CS) demonstrating prolonged activity against pyrethroid-resistant malaria vector mosquitoes, lasting up to 9 months [14,15]. This formulation subsequently served as the insecticide of choice for the majority of IRS programmes in sub-Saharan Africa [13] providing substantial control of mosquito vectors and malaria across distinct eco-epidemiological settings [6,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%